Microwave photonic filter using multiwavelength brillouin-erbium fiber laser - Loh, K.K.; Yeo, K.S.; Shee, Y.G.; Adikan, Faisal Rafiq Mahamd; Mahdi, M.A. (Institute of Electrical and Electronics Engineers (IEEE), 2015)
A microwave photonic filter based on multiwavelength Brillouin-erbium fiber laser (BEFL) is proposed and experimentally demonstrated. By precisely controlling the output channels of the BEFL, the 3-dB bandwidth of the filter spectrum can be adjusted at a resolution of similar to 24 MHz. The free spectral range of the filter can be tuned by changing the Brillouin gain fiber of the BEFL in addition to changing the length of the dispersion fiber, which adds flexibility to the filter system.